Small and medium enterprises and their financing patterns: evidence from Malaysia - Abdullah, Moha Asri; Ab. Manan, Siti Khadijah (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2011)
The contributions of small and medium enterprises (SMEs) to socio-economic developments have been long recognized, in developed and developing countries alike. In this relation, a wide range of support programmes have been introduced and implemented in many countries. Malaysia is not exceptional to this as various SMEs-oriented policies and SME support initiatives have been nationally initiated. Among the most important areas of support extended to SMEs are financial assistance and credit facilities. Nonetheless, earlier studies indicated that the SMEs’ outreach and accessibility to financial facilities, financing needs and pattern are different than of their larger firm counterpart. In view of this, this paper attempts to examine SMEs; their financing pattern and their accessibility to external debt finance based on 124 SMEs surveyed in Klang Valley, Malaysia. The findings revealed that start up SMEs do not require much external funding for set up, and besides they are commonly deficient of the means to obtain added funds. As SMEs grow and expand, the need for additional fund will arise, thus the external financial needs will start to increase even though the internal funds represent a significant proportion of their available funds. Among the SMEs that have obtained external finance, the amount and tenure of the funds tend to be small and short to medium terms respectively. The finding indicated that the age and assets of SMEs are insignificantly correlated to their accessibility to finance. Thus, the study concludes that a wide variety of financial facilities provided by various agencies and financial institutions lead to greater accessibility to finance SMEs in the country.